2011
DOI: 10.1186/1471-2180-11-55
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and virulence characteristics of an outer membrane-associated RTX exoprotein in Pasteurella pneumotropica

Abstract: BackgroundPasteurella pneumotropica is a ubiquitous bacterium that is frequently isolated from laboratory rodents and causes various clinical symptoms in immunodeficient animals. Currently two RTX toxins, PnxIA and PnxIIA, which are similar to hemolysin-like high-molecular-weight exoproteins are known in this species. In this study, we identified and analyzed a further RTX toxin named PnxIIIA and the corresponding type I secretion system.ResultsThe RTX exoprotein, PnxIIIA, contains only a few copies of the RTX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 42 publications
(45 reference statements)
1
20
0
Order By: Relevance
“…However, the virulence factors of bacterial infection in laboratory animals have not been thoroughly studied. Recently, we described the identification and characterization of the RTX toxins [19,21]. The P. pneumotropica animal model developed in this study will be useful for investigating virulence factors such as RTX toxin.…”
Section: Discussionmentioning
confidence: 98%
“…However, the virulence factors of bacterial infection in laboratory animals have not been thoroughly studied. Recently, we described the identification and characterization of the RTX toxins [19,21]. The P. pneumotropica animal model developed in this study will be useful for investigating virulence factors such as RTX toxin.…”
Section: Discussionmentioning
confidence: 98%
“…We are currently investigating the virulence factors of P. pneumotropica. In our previous studies, several RTX toxins have been identified in these bacteria [19,20]. Furthermore, several candidate virulence-associated genes such as RTX toxins were identified from a draft genome sequence of P. pneumotropica [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…The strain possessed outermost surface materials, which may be pili, on the bacterial cells and belonged to group two based on biochemical and genetic characteristics [17,18]. This strain produces RTX toxins PnxIA, IIA, and IIIA, and its draft genome sequence has been revealed [19,20]. The strain was thawed from frozen stocks (-80°C) and grown overnight on 5% horse blood agar plates (Sanko Junyaku Co. Ltd, Tokyo, Japan) and checked for purity.…”
Section: Preparation Of P Pneumotropica Inoculummentioning
confidence: 99%
“…In current studies, several RTX (repeats in toxin) toxins were identified in this species, and of these, 250-kDa PnxI-IIA contains bacterial Ig-like domains and hemagglutinin repeats that are thought to be indispensable for the protein's attachment and invasion of bacterial cells into host organs [15,16]. In fact, the recombinant PnxIIIA that lacks these domains failed to bind to the extracellular matrix (ECM) [16].…”
Section: Introductionmentioning
confidence: 97%
“…In current studies, several RTX (repeats in toxin) toxins were identified in this species, and of these, 250-kDa PnxI-IIA contains bacterial Ig-like domains and hemagglutinin repeats that are thought to be indispensable for the protein's attachment and invasion of bacterial cells into host organs [15,16]. In fact, the recombinant PnxIIIA that lacks these domains failed to bind to the extracellular matrix (ECM) [16]. PnxIIIA is reportedly less cytotoxic toward leukocytes as compared to other RTX family proteins, and therefore, PnxIIIA is one of the candidate antigens for immunization against P. pneumotropica infection in rodents [15,16].…”
Section: Introductionmentioning
confidence: 99%